Eight‐element self‐decoupled MIMO antenna design for 5G smartphones. Issue 3 (3rd January 2021) - Fu, Zhenning; Shen, Wenhui
Abstract: A self‐decoupled antenna element working at half‐ wavelength mode is proposed and implied into an eight‐element multiple‐input‐multiple‐output (MIMO) antenna array for the fifth‐generation (5G) smartphones applications. Particularly, self‐ decoupled is conveyed by the feature of balanced antenna, which is composed of an open slot (0.197 λ 0 × 0.035 λ 0 at 3.5 GHz) excited by a two‐arm feedline located on the horizontal ground board and a half‐wavelength dipole‐type mode is formed. A week ground current effect and high‐isolation level are achieved with no additional decoupling stub. Besides, the location of the element is thoroughly considered to achieve a desirable decoupling effect. In the desired 3.5 GHz band (3.4‐3.6 GHz), isolation of more than 18.5 dB and total efficiency of more than 65% are obtained. The proposed MIMO antenna was simulated and fabricated. The corresponding performances were claimed by simulated results and measured ones, a good uniformity between the two was obtained.